(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
In the present study, a new model of hybrid deep beams has been proposed and discussed. Six specimens are tested experimentally with two types of loading which are one-point and two-point loading and two hybridization models for concrete section. It is aimed from this study to search for the optimum distribution of the concrete types of the hybrid deep beams such that the lowest cost and weight to be reached with keeping the capacity without significant reduction. All specimens had the same dimensions, overall span of 1700 mm, 180 mm wide and 450 mm overall depth and the same steel reinforcement details. Results showed an increase in the capacity in the horizontal and the arched hybrid model by 27.6% and 39%, respectively, with one-point system. Moreover, toughness, enhanced by 44% and 131% for the two models respectively whereas, stiffness enhanced by 6.5% and 34.2% respectively and ductility enhanced by 0% and 31.2% respectively. For tests under two point loads, capacity enhanced by 34% and 36.9%, respectively, Toughness increased by 188% and 301% respectively. Stiffness enhanced by 7.5% and 29.4% respectively. Ductility enhanced by 40.3% and 95.1% respectively.